Una teoría cognitiva integral para la recuperación de información: saliendo del entorno del laboratorio - Ingwersen, Peter; Järvelin, Kalervo (Revista General de Información y Documentación, 2009)
The paper demonstrates how the Laboratory Research Framework fits into the integrated Cognitive Framework for IR. It first discusses the Laboratory Framework with emphasis on its underlying assumptions and known limitations. This is followed by a view of interaction and relevance phenomena associated with IR evaluation and central to the understanding of IR. The ensuing section outlines how interactive IR is viewed from a Cognitive Framework, and ‘light’ interactive IR experiments are suggested performed by drawing on the latter framework’s contextual possibilities. These include independent variables drawn from a collection, matching principles in a retrieval system, and the searcher’s situation and task context. The paper ends with concluding points of summarization of issues encountered.
Keywords: Information retrieval theory; Cognitive Research framework; Laboratory Framework; IR interaction; Relevance in IR; Research variables